Protection and adoption of abandoned children in Malaysia: comparative overview with Islamic law - Mohd, Azizah (2010)
Abandoned Child or the foundling in general refers to a child who is abandoned by his parents or guardian and his status is unknown. Issue on abandoned children (foundlings) is not new in Malaysia. It has come to attention and discussion since 1980. Despite enactment and amendment of law on child protection, statistics have shown the increased number of abandoned babies. Research has also been done to identify causes and reasons of abandonment which include adultery and illegitimacy. Islamic law among others has imposed a stern punishment on adultery with the purpose of deterring people from committing the offence.